PERAN BUDAYA BIROKRASI DALAM PENGEMBANGAN TATA KELOLA PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) - TITIK DJUMIARTI, TITIK DJUMIARTI (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
AbstractThe bureaucratic reform in a country basicaly reflects the interaction between value promiseand factual promise. In Indonesian that bureaucracy is signified by the coexistence betweenWeberian bureaucracy which originates from the west and the traditional bureaucracy which has itsroots in the socio-cultural aspects of the place. The reform bureaucracy must point three aspects thephenomenon or the shape which culture revitalition bureaucration with aspect behaviour approach,institutional approach and social-political system approach.Key words: Weberian bureaucracy, traditional bureaucracy, behaviour approach, institutionalapproach and social-political system approach.